96 Using quality improvement methodology to eliminate harm to GOSH patients through standardised devices and enhanced resources. (30th November 2020) - Huggins, Karleen; Wilson, Nicola; Wyan, Donna; Knott, Craig; Dunn, Helen; Andesson, Johanna; Ryan, Karen; Gee, Catherine
Abstract : Background: In 2019 GOSH identified variations in urethral catheter insertion and urinary catheter care. Datix highlighted this contributed to 28 potentially avoidable patient safety incidents in the previous 18 months. Lack of standardisation across the Trust was due to factors including; misbelief around female nurses catheterising males, patients having NG tubes inserted and multiple brands Trust-wide. The aim: Eliminate harm to ureteral catheterised patients. Methods: Supported by the Quality Improvement team, a Steering committee was formed from stakeholders Trust-wide. Reviewing incidents to identify themes and interventions, using the Model for Improvement (QI Tool), three work streams were established. Standardised pathway for catheter care: Developing clinical practice guidelines for Urinary Catheterisation, standardising electronic documentation across the MDTs and introducing an escalation pathway. Standardised trust training package: Quick reference posters, FAQs, Insertion videos and a Resources hub for quick/easy access. Facilitating 'Train the trainer study day' to improve overall nursing/medical knowledge. Standardised devices: Standardised brands and devices then developing a device size reference guide. The Project Plan kept focus on the aim and monitored time-dependant tasks. Measurements; Catheter related incidences, Urology referrals for catheterisation (normal anatomy) and nursing staff knowledge on catheter cares. Results: Completed - Workstreams 1&2, with a clear pathway, standardised electronic documentation, Trust-wide training package and a suite of resources. Workstream 3 still in progress, with an agreement to consolidate to two preferred devices Discussion: Our success is based on multidisciplinary working, using QI methodology and tools (Driver Diagrams) to identify primary drivers and simultaneously make decisions on how to improve care for catheterised patients. *Covid has impacted results but initial findings support our prediction that access to resources increases knowledge and skill, resulting in an impact on incidents. Conclusion: Staff now have all the resources needed to provide excellent care for catheterised patients. **No ethical clearance needed